Comparative saving behavior of rural and urban households in the Philippines - Bautista, Romeo M.; Lamberte, Mario B. (1990)
Marginal saving rates for the Philippine households are estimated, distinguishing between rural and urban households, by region and by income group. At a given income level, rural households generally save more, both on the average and on the margin. This contrasts with the higher savings rate for urban households in various regions, attributable for their higher incomes. Marginal savings rate for rural households are higher than for their urban counterparts. Faster growth of rural income need not result in lower aggregate savings.